2019
DOI: 10.3390/microorganisms7100473
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bacterial Community Changes during Vermicomposting of Grape Marc Derived from Red Winemaking

Abstract: Previous studies dealing with changes in microbial communities during vermicomposting were mostly performed at lab-scale conditions and by using low-throughput techniques. Therefore, we sought to characterize the bacterial succession during the vermicomposting of grape marc over a period of 91 days in a pilot-scale vermireactor. Samples were taken at the initiation of vermicomposting, and days 14, 28, 42, and 91, representing both active and mature stages of vermicomposting. By using 16S rRNA high-throughput s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
5
19
2
Order By: Relevance
“…This phylum is considered a fast-growing copiotroph group, while oligotrophic groups such as Actinobacteria, Planctomycetes, Verrucomicrobia and Chloroflexi reached higher levels on day 14, and the four of them, except for Actinobacteria, remained unchanged for the duration of the trial with distilled grape marc (Figure 3). Similarly, a rapid increase in Actinobacteria was found by Kolbe et al [25] on day 7, while Gómez-Brandón et al [7] observed a significant reduction in its abundance on day 14. Oligotrophic and copiotrophic bacterial groups mainly differed with regard to their growth strategies under nutrient rich conditions and their efficiency in metabolizing carbon substrates, i.e., labile and recalcitrant compounds for copiotrophs and oligotrophs, respectively [44].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This phylum is considered a fast-growing copiotroph group, while oligotrophic groups such as Actinobacteria, Planctomycetes, Verrucomicrobia and Chloroflexi reached higher levels on day 14, and the four of them, except for Actinobacteria, remained unchanged for the duration of the trial with distilled grape marc (Figure 3). Similarly, a rapid increase in Actinobacteria was found by Kolbe et al [25] on day 7, while Gómez-Brandón et al [7] observed a significant reduction in its abundance on day 14. Oligotrophic and copiotrophic bacterial groups mainly differed with regard to their growth strategies under nutrient rich conditions and their efficiency in metabolizing carbon substrates, i.e., labile and recalcitrant compounds for copiotrophs and oligotrophs, respectively [44].…”
Section: Discussionmentioning
confidence: 57%
“…Co-composting of distilled grape marc with other organic materials like green waste has been shown as a more effective alternative improving not only the compost quality but also shortening the time required to achieve stabilization [14]. Vermicomposting has also been successfully used to dispose of and treat large quantities of raw grape marc [2][3][4][5][6][7]16,17]. On the one hand, it may provide a means to neutralize the pH of this winery byproduct, as previously shown by Domínguez et al [2].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Traditional work centered around cultured strains, mycorrhizae, and non-sequence-based methods of assessing microbial community structure [4]. More recently, sequencing-dependent analysis have become available that investigate changes in the microbiome during composting [22] and pathogen-vermicompost interactions [23]. Here, we investigate the impact of VC-extract treatments on bacterial microbiome assembly in each peat-and soil-grown tomato rhizospheres.…”
Section: Introductionmentioning
confidence: 99%